Republic of Palau : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2004)
The Republic of Palau (Palau) has always been heavily dependent on external assistance. The availability of steady grants has allowed Palau to maintain a sizable public sector. A number of issues are considered in designing a comprehensive management strategy for the Compact Trust Fund (CTF). The following statistical data are also included in this paper: social indicators, financial position of compact trust fund, imports by product category, by country, or territory of origin, balance of payments, and so on.